TENSILE UPLIFT CAPACITY AND FAILURE MECHANISMS OF SCREW-PILE ANCHORS IN CLAY SOIL UNDER REPEATED LOADING - Munirwansyah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study investigates the tensile uplift capacity of screw piles in clay soil as an alternative anchoring system for slope stabilization in cohesive ground conditions. The research aims to address the limited availability of empirical field data on screw-pile behavior under repeated loading and to evaluate the agreement between theoretical predictions and actual in situ responses. The methodology employs an experimental approach through in situ testing with screw-pile diameters of 10 cm, 15 cm, and 20 cm, and embedment depths ranging from 0.6 m to 1.0 m. The tests were conducted under both static and repeated tensile loading using a hydraulic jack system, accompanied by vertical deformation measurements to establish load–displacement curves. Theoretical capacity was calculated using a limit equilibrium approach for comparison with experimental results. The findings reveal a nonlinear load–displacement response, characterized by initial stiffness followed by progressive deformation into the post-yield stage. At a maximum load of 2.858 tons, deformation increased with diameter, from 5.10 cm (10 cm) to 8.49 cm (20 cm). Under repeated loading, failure occurred at a lower load of approximately 1.6 tons with a maximum deformation of 1.648 cm, indicating potential capacity degradation due to cyclic loading. The comparison between theoretical and field results shows significant deviations, with analytical predictions generally underestimating the in situ capacity. This highlights the limitations of simplified models that do not fully account for shaft adhesion, installation disturbance, soil heterogeneity, pore-water pressure effects, and cyclic degradation. Overall, this study contributes valuable field pull-out test data for screw piles in clay under repeated loading, emphasizing the need for design calibration based on full-scale testing for slope stabilization applications. The results also suggest opportunities for further research involving long-term monitoring and advanced modeling of cyclic degradation.